(3GdbHV Ydi GdeJge aj GdJTQjYjf GddjHi h GdeUQi (B: s (3OQGSI ebGQfI (B/ s - (3QeVGf Ydi jYbhH LGO Gddgs; (3MSfjf EHQGgje UGdM YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3dG LOGd aj chf GdMQjI gj eMhQ GQJcGR GdCee h GdMVGQGJ (B: (3h ef gfG GgJeJ GdOSGJjQ HGdMQjGJ (B: (3h cadJ UjGfI GdMbhb GdYGeI ddaQO (B: (3h bQQJ Cf GdMQjI GdTNUjI Mb WHjYj (B: (3h gj eUhfI dG JeS(B. (3h jYJHQ GdbHV ef GdehVhYGJ GdgGeI aj bGfhf GdELQGAGJ GdLfGFjI (B: (3dCfg jTcd eSGSG eHGTQG HMQjI GdeJge (B: (3h gh HPdc jTcd JYGQVG eY eHOC bQjfg GdHQGAI(B: (3hjdhM gPG GdJYGQV ef NdGd Cf ELQGA GdbHV jCJj eSHbG Ydi KHhJ NdGa GdCUd (B: (3aeVehf GdbHV jYfi bjO MQjI GdaQO (B: (3h eG jdMb Pdc ef bShI gPG GdELQGA HeG jdMbg HGdeJge ef CVQGQs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B228-243s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjYjf GddjHi h GdeUQis; (3GdbGfhf GdLfGFis; (3GdbHV Ydi GdeJges; (3eHQQGJ GdbHVs; (3GMhGd GdbHV Ydj GdeJges; (3GdbHV aj GdGMhGd GdYGOjIs; (3GdbHV aj GMhGd GdJdHSs; (3GKGQ GdbHV GdUMjM s; (3HWdGf GdbHVs; (3GdeSFhdjI Yf GdbHV ZjQ GdeTQhYs; (3GdbHV hGdMHS GdGMJjGWjs; (3GdbHV hGdGYJbGd GdGOGQjs; (3GdbHV hGdGSJjbGas; (3MGdGJ GdJdHS hTQhWgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs